STUDIES ON THE BEHAVIORAL IMPACT OF VISITORS AND FEEDING MANAGEMENT IN HOG DEER (AXIS PORCINUS) KEPT AT JALLO WILDLIFE PARK, LAHORE - ALI, I; NOREEN, M; RASHEED, S; HUSSAIN, A; SAEED, I (Biological and Clinical Sciences Research Journal, 2024)
This study was conducted to observe the behavioral impact of visitors and feeding management in Hog Deer (Axis porcinus) kept at Jallo Wildlife Park, Lahore. In this study, 20 animals of hog deer approximately of the same age of both sexes were included. The animals were divided into four experimental groups consisting of five animals (Hog Deer) in each group such as Group A (Control) with addition of no formulated feed, Group B containing 0.25 kg formulated feed per animal per day, Group C containing 0.30 kg formulated feed per animal per day, Group D containing 0.40 kg formulated feed per animal per day. The animals were fed in groups of five in each stall with a combined feeding pen. A composite feed /ration was prepared mechanically at the farm and was offered to the animals. This experiment was comprised in the 8th week. The feeding behavior and the weight gain were recorded weekly. After the complication of experiments highest growth was observed in Group D animals supplemented with 0.40 kg/animal/day formulated feed. The obtained result showed that high visiting of humans change the feeding behavior of Hog Deer as they mostly showed high locomotion instead of feeding. It is suggested that proper management care is required to keep the hog deer in healthy conditions during captivity and avoid overcrowding of visitors for negative influence on their habitat and feed.